2021
DOI: 10.1002/mbo3.1160
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic potential of the moderate halophile Yangia sp. ND199 for co‐production of polyhydroxyalkanoates and exopolysaccharides

Abstract: Yangia sp. ND199 is a moderately halophilic bacterium isolated from mangrove samples in Northern Vietnam, which was earlier reported to grow on several sugars and glycerol to accumulate poly(hydroxyalkanoates) (PHA). In this study, the potential of the bacterium for co‐production of exopolysaccharides (EPS) and PHA was investigated. Genome sequence analysis of the closely related Yangia sp. CCB‐M3 isolated from mangroves in Malaysia revealed genes encoding enzymes participating in different EPS biosynthetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…All the cultivations were performed in 50-mL bottles containing 22 mL of the medium and inoculated with 3 mL of a cell suspension with initial OD 620 of 2.1. The bottles were sealed with rubber caps, and the cultivation was run at 30 • C and 100 rpm for 48 h. Samples were withdrawn at regular intervals for analyses of cell growth and EPS production as previously reported [35,36]. All experiments were carried out in duplicates.…”
Section: Cultivation Of the Bacterial Isolate Bu-4mentioning
confidence: 99%
See 2 more Smart Citations
“…All the cultivations were performed in 50-mL bottles containing 22 mL of the medium and inoculated with 3 mL of a cell suspension with initial OD 620 of 2.1. The bottles were sealed with rubber caps, and the cultivation was run at 30 • C and 100 rpm for 48 h. Samples were withdrawn at regular intervals for analyses of cell growth and EPS production as previously reported [35,36]. All experiments were carried out in duplicates.…”
Section: Cultivation Of the Bacterial Isolate Bu-4mentioning
confidence: 99%
“…Cell growth was determined by measuring the optical density (OD) at 620 nm with a spectrophotometer (UV 1800, Shimadzu, Japan) as previously reported [35]. Culture samples (500 µL) were centrifuged at 16,900× g for 5 min, diluted with 4.5 mL of acidified water (with H 2 SO 4 ), and stirred for 10 s. Each sample was filtered through a 20 µm filter, and sugar consumption was analyzed by HPLC using an Aminex HPX-87H column (Bio-Rad, Hercules, CA, USA) coupled to a Prominence HPLC system (Shimadzu Corp., Kyoto, Japan), equipped with a CBM-20A system controller, an isocratic pump (LC-30AD), a refractive index detector (RID-20A), a column oven (CTO-10 ASVP), a degasser (DGU-20A), and an autosampler (SIL-30AC).…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we tested the impact of various carbon sources on EPS yield and MW ( Figure 2 a,b). Ammonium chloride (100 mM) was chosen as the nitrogen source according to other studies [ 30 , 31 , 32 ]. Various carbon sources were used: glucose, sucrose, lactose, lactate, glycerol, and mannitol at 30 g L −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Few examples are the simultaneous synthesis of 5AVA and glutarate by Corynebacterium glutamicum ( Rohles et al, 2016 ; Haupka et al, 2020 ), β-glucan and pullulan by engineering Aureobasidium pullulans ( Wang G.-L. et al, 2020 ), acetoin and succinic acid by Enterobacter cloacae ( Su et al, 2021 ), polyhydroxyalkanoates and exopolysaccharides by Yangia sp. ND199 ( Romero Soto et al, 2021 ), and xylitol and ethanol by yeast strains ( Shankar et al, 2020 ). Lopez-Hidalgo et al reported that the engineered strain increased 30% the coproduction of ethanol and hydrogen used wheat straw and corn stover as feedstock ( Lopez-Hidalgo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%